Menganalisis Bentuk dan Fungsi Verba dalam Cerita Rakyat “Si Buyung Besar” - Simaremare , Juni Agus; Siregar, Rumada; Silalahi, Laura; Nahampun, Rinaldi (IdeBahasa, 2023)
The aim of this research is to describe the form and function of verbs in the folktale "Si Buyung Besar". The method used in this research is literature. The data collection technique in this research is the technique of reading, taking notes and managing the content of the story. The data source that researchers used in the research was the story "Si Buyung Besar". The results of this research show that the verb forms in the story "Si Buyung Besar" are departing, arriving, ringing, flocking, changing, welcoming, shaking hands, greeted, answering, welcoming, admiring, proud, going home, paying attention, and running. The functions of the verbs found in the story "Si Buyung Besar" are function as predicate, function as object, function as subject, function as information, function as complement.